2016
DOI: 10.1177/1098612x16661375
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of parvoviruses from domestic cats reveals emergence of newer variants in India

Abstract: Objectives The present study was undertaken to characterise the viral polypeptide 2 (VP2) gene of parvovirus from domestic cats in India. Methods The faecal samples from diarrhoeic/healthy domestic cats were collected from different geographical regions of India for screening by PCR assay followed by sequence analysis of the VP2 gene. Results Canine parvovirus (CPV)/feline panleukopenia virus (FPV) infections were found in 12 (11.3%) of 106 faecal samples tested. Two new CPV-2a (297Ala and Asn426) and three FP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…To understand the evolutionary importance of the mutations found in CPV-2a and CPV-2b variants, an analysis was performed to determine the positive selection sites (Supplementary Table S1). Our results confirmed for CPV-2b, that sites 324 and 440 have a strong positive selection, as previously reported in Asian CPV-2 variants [37,38], which are related to the Colombian CPV-2b variant. In the case of CPV-2a, the positive selection sites were 297 and 324.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To understand the evolutionary importance of the mutations found in CPV-2a and CPV-2b variants, an analysis was performed to determine the positive selection sites (Supplementary Table S1). Our results confirmed for CPV-2b, that sites 324 and 440 have a strong positive selection, as previously reported in Asian CPV-2 variants [37,38], which are related to the Colombian CPV-2b variant. In the case of CPV-2a, the positive selection sites were 297 and 324.…”
Section: Discussionsupporting
confidence: 91%
“…Both the CPV-2a and the CPV-2b variant found in our study present the 324Ile mutation (Table 2; Supplementary Figure S2). This change has been previously reported in cats infected with CPV-2a [38], evidencing that it is an important amino acid in determining host range. Additionally, it has been recently shown that this amino acid residue is close to the virus-receptor interaction domain and that few structural changes are required in CPV-2 to be able to adapt and interact with TfR receptors from different species [34].…”
Section: Discussionsupporting
confidence: 75%
“…Feline panleukopenia virus and CPV infection of vaccinated cats and dogs have been reported and the viruses have been isolated from diarrhoeic animals (Decaro et al., ; Mukhopadhyay et al., ). To gain a better understanding of the importance of cats as a potential source of genetic diversity for parvoviruses, parvovirus strains detected in cats with gastroenteritis signs were analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, CPV variants were retrieved from cats with FPL-like disease in Italy, Germany, USA, Japan, India, Portugal, and Spain [24,47,52,53,55,56,[58][59][60][61]70,71] Interestingly, as cats are susceptible to both CPV variants and FPV, superinfection and co-infection with multiple Carnivore protoparvovirus 1 strains may occur, potentially facilitating the recombination and high genetic heterogeneity of these viruses. Indeed, the detection of mixed FPV/CPV infections in cats, associated or not with clinical signs, emphasizes the possible role of cats as a source of new variants of parvoviruses, with concrete problems for the implementation of prophylaxis [55,[59][60][61].…”
Section: Protoparvovirusesmentioning
confidence: 99%